The informational and organizational providing for exposure of psychophysiological disadaptation of students - V. A. Yudin; P. N. Ketov; S. I. Karas; O. N. Loguntsova; M. N. Baranova; T. Yu. Grachyova (Бюллетень сибирской медицины)
In the article the data of organization and informational support of student’s psychophysiological disadaptation revelation program has been presented. Under the statistical treatment the features that are informative for such state screening have been revealed.